Fingolimod-associated PML with mild IRIS in MS: A clinicopathologic study. Issue 1 (January 2018) - Nishiyama, Shuhei; Misu, Tatsuro; Shishido-Hara, Yukiko; Nakamichi, Kazuo; Saijo, Masayuki; Takai, Yoshiki; Takei, Kentarou; Yamamoto, Naoki; Kuroda, Hiroshi; Saito, Ryuta; Watanabe, Mika; Tominaga, Teiji; et al.
Abstract : Objective: To clarify the clinical, neuropathologic, and virologic characteristics of progressive multifocal leukoencephalopathy (PML) and its immune reconstitution inflammatory syndrome (IRIS) in a patient with fingolimod-treated MS. Methods: A case study. Results: A 34-year-old patient with MS using fingolimod for 4 years had a gradual progression of right hemiparesis and aphasia with a new subcortical white matter lesion in the precentral gyrus by initial MRI. Blood tests were normal, except for lymphopenia (160 cells/μL). One month after the cessation of fingolimod, brain MRI depicted a diffusely exacerbated hyperintensity on fluid-attenuated inversion recovery and diffusion-weighed imaging in the white matter with punctate gadolinium enhancement, suggesting PML-IRIS. A very low level of JC virus (JCV)-DNA (15 copies/mL) was detected in the CSF as judged by quantitative PCR. Brain tissues were biopsied from the left frontal lesion, which showed some small demyelinated foci with predominant loss of myelin-associated glycoprotein with infiltrations of lymphocytes and macrophages, but clear viral inclusion was not observed with hematoxylin-eosin staining. JCV-DNA was uniquely detectable in an active inflammatory demyelinating lesion by in situ hybridization, possibly suggesting an early phase of PML. DNA extracted from the brain sample was positive for JCV-DNA (151 copies/cell). It took 3 months to normalize the blood lymphocyte count. The patient was treated with 1 g of IV methylprednisolone for 3 days and a weekly oral dose (375 mg) of mefloquine, and her symptoms gradually improved. Conclusion: Low CSF JCV-DNA and unfound viral inclusions initially made her diagnosis difficult. The clinical course of fingolimod-associated PML may be associated with mild immune reconstitution.